The AP2/ERF transcription factor OfERF2 promotes flavonoid biosynthesis in Osmanthus fragrans - Hai, Xiangzhan; Liu, Gege; Lu, Miaomiao; Fan, Rong; Li, Ke; Guo, Bingao; Zhang, Huijuan; Shang, Fude; Han, Yuanji (Tree genetics & genomes, 2025)
Sweet osmanthus is a traditional Chinese flower with abundant flavonoids in its petals. However, the regulatory mechanisms that produce these flavonoids remain unclear. Metabolomic analysis results revealed that 15 compounds in ‘Chenghong Dangui’ petals were upregulated compared to those in ‘Zaohuang’ petals. One AP2/ERF transcription factor gene in ‘Chenghong Dangui’ petals, OfERF2 , was upregulated. Overexpression of OfERF2 in tobacco upregulated the expression of NbC4H , Nb4CL , NbCHS , NbCHI , NbF3H , and NbFLS . Ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS) analysis showed that 41 flavonoids, including 28 flavonol compounds, were upregulated in tobacco leaves transfected with OfERF2 . Chromatin immunoprecipitation sequencing (ChIP-Seq) analysis results indicated that the transcription factor OfERF2 could bind to the promoters of OfCHS and OfFLS , which are key genes in the flavonoid biosynthetic pathway in sweet osmanthus. The overexpression of OfERF2 in sweet osmanthus petals considerably upregulated the expression of OfCHS and OfFLS . The results of tobacco transformation, dual-luciferase reporter assays, and electrophoretic mobility shift assays indicated that OfERF2 could bind to GCC-box elements in the promoter regions of OfCHS and OfFLS , thereby activating them and promoting gene expression. This study provides an important theoretical basis for genetic improvement and breeding related to flavonoid metabolism in sweet osmanthus plants.